Timeliness of 24 childhood immunisations and evolution of vaccination delay: Analysis of data from 54 low- and middle-income countries. - Nieves Derqui; Isobel M Blake; Elizabeth J Gray; Laura V Cooper; Nicholas C Grassly; Margarita Pons-Salort; Katy A M Gaythorpe (Public Library of Science (PLoS), 2024)
Vaccination timeliness is often not considered among standard performance indicators of routine vaccination programmes, such as vaccination coverage, yet quantifying vaccination delay could inform policies to promote in-time vaccination and help design vaccination schedules. Here, we analysed vaccination timeliness for 24 routine childhood immunisations for 54 countries. We extracted individual vaccination status and timing from Demographic and Health Surveys data from 54 countries with surveys from 2010 onwards. Individual data was used to estimate age at vaccination for <5 year-old children. Recommended age of vaccination for each country and vaccine was compared to the age at vaccination to determine vaccination delay. The evolution of vaccination delay over time was described using estimates from different birth cohorts. To identify socio-demographic indicators associated with delayed vaccination, we used multivariable Cox regression models with country as random effect and estimated the Hazard Ratio for vaccination with each vaccine-dose for each week post recommended vaccination age. Vaccine coverage at the recommended age was highest for birth and first doses (e.g. 50.5% BCG, 18.5% DTP-D1) and lowest for later doses (e.g. 5.5% DTP-D3, 16.3% MCV-D1, 8.2% MCV-D2). Median delay was lowest for birth doses, e.g. BCG (1 week (IQR: 0 to 4)), and it increased with later doses in vaccination courses: 1 (0, 4) week for DTP-D1 versus 4 (2, 9) weeks for DTP-D3. Although the median delay for each vaccine-dose remained largely constant over time, the range of delay estimates moderately decreased. Children living in rural areas, their countries' poorer wealth quintiles and whose mothers had no formal education were more likely to received delayed vaccinations. Although we report most children are vaccinated within the recommended age window, we found little reduction on routine immunisation delays over the last decade and that children from deprived socioeconomic backgrounds are more likely to receive delayed vaccinations.